Xenosterolemia in clinical practice: what is in a name?. Issue 2 (29th April 2023) - Loh, Wann Jia; Watts, Gerald F.
Abstract : Purpose of review: The aim of this study was to assess the potential value of the measurement of plasma xenosterols (or phytosterols) concentrations in clinical practice. Recent findings: Recent genetic studies suggest that individuals with elevated plasma phytosterol concentrations due to monogenic and polygenic variants are at an increased risk of coronary artery disease. This supports early observations that elevated plasma phytosterol concentrations are per se atherogenic. Summary: Measurement of plasma phytosterols can identify individuals with xenosterolemia (or phytosterolemia). This may be clinically useful in four ways: Establishing a diagnosis and informing management of patients with homozygous phytosterolemia; Providing a comprehensive differential diagnosis for familial hypercholesterolemia; Providing an index of cholesterol absorption that may inform personalized pharmacotherapy; and Informing more precise assessment of risk of cardiovascular disease.